Evaluation of chemical compounds as repellents of the brown marmorated stink bug (Halyomorpha halys [Stål]) - Ziga Laznik; Matej Podgornik Milosavljević; Stanislav Trdan (Plant Protection Science)
The brown marmorated stink bug [Halyomorpha halys (Stål)] is an invasive pest species. This polyphagous insect, native to Eastern Asia, threatens various cultivated plant species. Control methods often rely on chemical insecticides, but the decreasing use of such agents has prompted a shift towards preventive measures. As a defence mechanism, natural compounds released by plants have gained attention for their potential deterrent or attractant properties. In this study, we evaluated the response of the brown marmorated stink bug to selected chemical substances, including citronellal, hexanal, nonanol, β-caryophyllene, linalool, ocimene, nerolidol, terpinolen, α-humulene, dimethyl sulfide, aggregation pheromone, and ethanol. The experiment was conducted using an olfactometer. Two experiments were performed, comparing the substances against dimethyl sulfoxide and then refining the selection based on initial results; in the first series, nerolidol, ocimene, and terpinolene exhibited promising results as complete deterrents. The second series confirmed nerolidol as the most effective deterrent among all tested substances. These findings contribute to developing preventive strategies for managing the brown marmorated stink bug and reducing reliance on chemical insecticides.